Strategies for the Conservation and Continuation of Spatial Context in Urban Renewal of Macau’s Historic Districts: A Case Study of the Barra & Manduco Area - Wu, Xueying; Yu, Shuo; Liu, Jie (International Journal of Social Sciences and Public Administration, 2024)
Amid the rapid urban development process, the preservation and revitalization of Macau’s historic districts and cultural heritage face significant challenges. This study aims to explore strategies for organizing and preserving the spatial context of the Barra & Manduco area within the framework of Macau’s urban renewal. Adopting an urban spatial perspective, the research analyzes the spatial characteristics of the district through the lenses of spatial power, spatial order, and spatial context. Based on the current state of the Barra & Manduco area, the study proposes strategies for the conservation and continuation of its spatial context from four aspects: street texture, visual control, integration of history and tourism, and local culture. These strategies aim to revitalize the historic district and reinvigorate its spatial and cultural vitality.